2011
DOI: 10.1007/s11663-011-9619-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Boron Compounds on the Corrosion Resistance of Andalusite-Based Low-Cement Castables in Contact with Molten Al Alloy

Abstract: Interfacial reactions between Al alloy and andalusite low-cement castables (LCCs) containing 5 wt pct B 2 O 3 , B 4 C, and BN were analyzed at 1123 K and 1433 K (850°C and 1160°C) using the Alcoa cup test. The results showed that the addition of boron-containing materials led to the formation of aluminoborate (9Al 2 O 3 .2B 2 O 3 ) and glassy phase containing boron in the prefiring temperature (1373 K [1100°C]), which consequently improved the corrosion resistance of the refractories. The high heat of formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Figure illustrates the microstructure of the spinel layer, which consists of Al alloy channels penetrating within the spinel grains and these act as a mass transfer pathway between the metal and ceramic, as has been observed in similar studies …”
Section: Resultssupporting
confidence: 53%
“…Figure illustrates the microstructure of the spinel layer, which consists of Al alloy channels penetrating within the spinel grains and these act as a mass transfer pathway between the metal and ceramic, as has been observed in similar studies …”
Section: Resultssupporting
confidence: 53%
“…Figure 4(b) shows that the porous spinel region is not homogeneous. The spinel is usually formed at the interfaces of molten Al-Mg alloys and aluminosilicate refractories, 3,7,8,10,24 although its influence on the refractory corrosion remains unclear. One study has suggested that dense spinel might act as a physical barrier against molten aluminum penetration.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is well‐known that the refractories are prone to gradual degradation owing to extensive reactions with molten aluminum and its alloys . Since the 1980s, antiwetting additives, such as BaSO 4 and CaF 2 , have been incorporated into aluminous and high‐alumina compositions to enhance the corrosion resistance . These additives increase the interface energy between the refractory component and molten aluminum alloy (σ LS : liquid‐solid interface energy) through the formation of new phases that establish physical barriers on the coarse grain surfaces, thereby decreasing the wetting of aluminosilicate refractories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigations confirm that the improvement in corrosion resistance is also achieved through the addition of boroncontaining compounds and this feature is attributed to the high stability of the aluminoborate phase [20]. Different calcium compounds (CaO, CaCO 3 , CaSO 4 , CaF 2 , clinker white cement, calcia feldspar, wollastonite and Ca 3 (PO 4 ) 2 ) were used as additives in andalusite-based low-cement castables in contact with a molten Al-alloy, demonstrating that the addition of white cement clinker and calcia feldspar to the matrix is effective in decreasing the penetration of molten Al.…”
Section: Introductionmentioning
confidence: 91%